Extra-Esophageal Pepsin from Stomach Refluxate Promoted Tonsil Hypertrophy. - Jin Hyun Kim; Han-Sin Jeong; Kyung Mi Kim; Ye Jin Lee; Myeong Hee Jung; Jung Je Park; Jin Pyeong Kim; Seung Hoon Woo (PLoS ONE, 2016)
Gastroesophageal reflux is associated with numerous pathologic conditions of the upper aerodigestive tract. Gastric pepsin within reflux contributes to immunologic reactions in the tonsil. In this study, we aimed to find the relationships between pepsin and tonsillar hypertrophy.We explored the notion whether tonsillar hypertrophy was due to pepsin-mediated gastric reflux in tonsil hypertrophy. Fifty-four children with tonsil hypertrophy and 30 adults with tonsillitis were recruited before surgical treatment. Blood and tonsil tissues from each patient were harvested for analysis of changes in lymphocyte and macrophage numbers coupled with histological and biochemical analysis. Pepsin was expressed at different levels in tonsil tissues from each tonsillar hypertrophy. Pepsin-positive cells were found in the crypt epithelium, surrounding the lymphoid follicle with developing fibrosis, and also surrounding the lymphoid follicle that faced the crypt. And also, pepsin staining was well correlated with damaged tonsillar squamous epithelium and TGF-β1 and iNOS expression in the tonsil section. In addition, pepsin and TGF-β1-positive cells were co-localized with CD68-positive cells in the crypt and surrounding germinal centers. In comparison of macrophage responsiveness to pepsin, peripheral blood mononuclear cells (PBMNCs) were noticeably larger in the presence of activated pepsin in the child group. Furthermore, CD11c and CD163-positive cells were significantly increased by activated pepsin. However, this was not seen for the culture of PBMNCs from the adult group.The lymphocytes and monocytes are in a highly proliferative state in the tonsillar hypertrophy and associated with increased expression of pro-inflammatory factors as a result of exposure to stomach reflux pepsin.